2022
DOI: 10.1128/aem.01970-21
|View full text |Cite
|
Sign up to set email alerts
|

Anaerobic Biodegradation of Chloroform and Dichloromethane with a Dehalobacter Enrichment Culture

Abstract: Chloroform (CF) and dichloromethane (DCM) are among the more commonly identified chlorinated aliphatic compounds found in contaminated soil and groundwater. Complete dechlorination of CF has been reported under anaerobic conditions by microbes that respire CF to DCM and others that biodegrade DCM. The objectives of this study were to ascertain if a commercially available bioaugmentation enrichment culture (KB-1® Plus CF) uses an oxidative or fermentative pathway for biodegradation of DCM; and to determine if t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
24
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(31 citation statements)
references
References 32 publications
2
24
0
1
Order By: Relevance
“…Surprisingly the values in the ABR where such CFM treated water was recycled remained at a value of 1–10 mg L −1 . It has been reported that anaerobic conditions favor biodegradation of chloroform 25 and additionally CFM is highly volatile, thus these factors may justify the low ABR values in the closed loop. The high CFM values produced by the ECR are thus not due to an accumulation effect.…”
Section: Resultsmentioning
confidence: 99%
“…Surprisingly the values in the ABR where such CFM treated water was recycled remained at a value of 1–10 mg L −1 . It has been reported that anaerobic conditions favor biodegradation of chloroform 25 and additionally CFM is highly volatile, thus these factors may justify the low ABR values in the closed loop. The high CFM values produced by the ECR are thus not due to an accumulation effect.…”
Section: Resultsmentioning
confidence: 99%
“…At contaminated sites in particular, it may enhance bioremediation, as the production of hydrogen, acetate, and ethanol can both stimulate microbial blooms or serve as secondary substrates for co-metabolism ( Horvath, 1972 ; Wrighton et al, 2014 ). Outside of necromass studies, similarly “self-feeding” mixed cultures have been described for dechlorination of trichloromethane and DCM ( Wang et al, 2022 ), chlorobenzene ( Liang et al, 2013 ), and 3-chlorobenzoate ( Dolfing, 1986 ; Dolfing and Tiedje, 1987 ). Consumption of dead biomass can also remineralize or liberate important nutrients including nitrogen, phosphorous, trace elements, and cobalamins ( Head et al, 2006 ; Christie-Oleza et al, 2017 ).…”
Section: Resultsmentioning
confidence: 99%
“…Microbial reductive dechlorination (halorespiration) requires carbon and electron sources to dechlorinate chlorinated solvents, using them as electron acceptors. However, halorespiration is mostly carried out by specialized bacteria not common in the environment (Wang et al, 2022). Application of nanoscale zero‐valent iron (Fe 0 ) has been used in soil and groundwater remediation (Jin et al, 2018; Lv et al, 2020; Zhu et al, 2021), where it acts as a reducing agent donating electrons to transform halogenated contaminants into less toxic forms.…”
Section: Introductionmentioning
confidence: 99%